2016
DOI: 10.1063/1.4951000
|View full text |Cite
|
Sign up to set email alerts
|

Single shot near edge x-ray absorption fine structure spectroscopy in the laboratory

Abstract: With the help of adapted off-axis reflection zone plates, near edge X-ray absorption fine structure spectra at the C and N K-absorption edge have been recorded using a single 1.2 ns long soft X-ray pulse. The transmission experiments were performed with a laser-produced plasma source in the laboratory rendering time resolved measurements feasible independent on large scale facilities. A resolving power of E/ΔE ∼ 950 at the respective edges could be demonstrated. A comparison of single shot spectra with those c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…[12][13][14][15] Despite the fact that interest in laboratory-based XAFS faded with the advent of thirdgeneration SR sources, the development of laboratory-based XAFS instrumentation continued steadily, [16][17][18][19][20][21][22][23][24][25][26] with a rapid increase in in-house XAFS applications in the last few years. [27][28][29][30][31][32][33][34][35][36] The XAFS spectrum of a sample can be measured by means of the transmission, fluorescence, or electron yield method. 37,38 In the transmission method, the energy of the incident beam is varied step by step and its intensity as well as the intensity of the transmitted beam are measured by ionization chambers or photodiodes.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] Despite the fact that interest in laboratory-based XAFS faded with the advent of thirdgeneration SR sources, the development of laboratory-based XAFS instrumentation continued steadily, [16][17][18][19][20][21][22][23][24][25][26] with a rapid increase in in-house XAFS applications in the last few years. [27][28][29][30][31][32][33][34][35][36] The XAFS spectrum of a sample can be measured by means of the transmission, fluorescence, or electron yield method. 37,38 In the transmission method, the energy of the incident beam is varied step by step and its intensity as well as the intensity of the transmitted beam are measured by ionization chambers or photodiodes.…”
Section: Introductionmentioning
confidence: 99%
“…Although, there has been considerable progress in the development of laboratoryscale so X-ray sources, such as laser-or discharge-produced plasmas [2][3][4][5][6][7][8] and high-order harmonics (HHG), 9-12 these sources have been employed for NEXAFS spectroscopy only a few times until now. [13][14][15][16][17][18][19] In addition, except for previous own work including pump-probe experiments 20 and investigations with samples at atmospheric pressure, 21 all these measurements were restricted to photon energies below 500 eV. Recently, Popmintchev et al 22 demonstrated NEXAFS investigations at the Kand L-absorption edges of solids in the near-keV range using a HHG source, ideally suited for dynamic probing of materials on an attosecond time scale.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, a single pulse (single-shot) has to be used for NEXAFS spectrum acquisition. A single-shot NEXAFS has been demonstrated recently using a laser plasma light source based on a solid target [ 19 ]. However, solid targets that are known to produce debris associated with laser ablation products, which is a highly undesirable effect.…”
Section: Introductionmentioning
confidence: 99%